MORTALITY AND MORBIDITY PROFILE IN ELBW AND VLBW NEONATES IN A TERTIARY CARE SETUP: A RETROSPECTIVE OBSERVATIONAL STUDY. - Panigrahi, Bineet; Pradhan, Payal; Sahoo, Devi Prasad; Mohapatra, Bhagyashree (Student’s Journal of Health Research Africa, 2024)
Background Below 5 years of age globally half of the children are dying in the first month of life. The neonatal period accounts for 2.4 million/annum deaths globally. Low birth weight (< 2500 grams) is often associated with mortality and morbidity. The study analyzed the morbidity and mortality profiles of ELBW and VLBW neonates. Method The study was conducted as a retrospective observational study in the Department of Neonatology. Preterm babies with low birth weight were considered for this study. Maternal characteristics and neonatal characteristics were recorded. They were followed up for 28 days from the day of birth. All the complications developed, treatment, and outcomes were recorded during this period. Results In this study, 96 neonates with less than 1500 grams of birth weight were studied retrospectively over the last 2 years of data. The mortality rate of ELBW babies was 47.6%, that of VLBW babies excluding ELBW was 8%, and 2 babies were gone for LAMA. The death rate in babies with gestational age in weeks≤24, 25-26, 27-28, 29-32, 33-35, and >35 was 80%, 80%, 16.6%, 1.3%, 14.3%, and 75%, respectively. The most common cause of death in VLBW neonates is sepsis, with pulmonary hemorrhage being 25% each, followed by respiratory distress syndrome, severe intraventricular hemorrhage, and perinatal asphyxia being 18.75%, 18.75%, and 12.5%. Conclusion ELBW newborns have a higher probability of mortality and morbidity when associated with other complications such as pulmonary hemorrhage, RDS, and sepsis compared to LBW newborns. Recommendation The long-term follow-up done at the NICHD wherein the network is developed so that the tracking of the ELBW infants is assured decreases the mortality significantly. Such tracking networks and follow-up of the ELBW patients are required.